EVOLUTION OF ADVERTISING WITH A SPECIFIC RETROSPECTION AT SPORT ADVERTISING - Duško Bjelica; Stevo Popović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
The objective of this study represent the evolution of advertising, while the main goal will be directional to evoluation of general advertising with a specific retrospection at sport advertising. The main tasks of this study are, the first explaining the interesting evoluation of the advertising in general as well as drawing attention to the specific nature of the sport advertising as a separate field of advertising in general. Method: During the making of this study, the author used descriptive method with consulting of competent literature. The previous author' experience in this field was also so useful. Moreover, the author used the analytic method and parallel method that is the most productive if you make some inferences about some appearance. Results: Sport advertising did not develop separately, but it represents an integral part of the overall advertising that has much deeper roots in the history of mankind. This study made general retrospection of common characteristics and differences that might be relevant for many researchers in this area. Discussion: Sport advertising is developing rapidly around the world, the dominant example of this development is most evident in the "advertising industry" in the United States (Popović, 2011). However, the sport advertising is not at the expectable level in Montenegro, mostly due to the reason the "advertising industry" in the country is not developed yet. Hence, some further knowledge collected in this study might improve the contemporary situation and help the current and potential advertisers to invest in sport industry.